A process for the production of a specific pore size aluminum foam

By using a combination of composite foaming agent and stearic acid, the problems of poor pore size adjustment and uniformity in melt foaming method are solved, and the uniformity of pore size distribution and mechanical strength are improved, making it suitable for preparing high-performance aluminum foam materials.

CN120818715BActive Publication Date: 2026-01-23CHONGQING UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511055171.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-30
Publication Date
2026-01-23
Estimated Expiration
2045-07-30

AI Technical Summary

Technical Problem

In the prior art, when preparing closed-cell aluminum foam using the melt foaming method, the foaming performance of the foaming agent is uncontrollable, resulting in difficulty in adjusting the pore size, poor pore size distribution and size uniformity, which affects the mechanical strength and thermophysical properties of the material.

Method used

The composite foaming agent is composed of titanium hydride, zirconium hydride and calcite. Combined with stearic acid, it reduces the surface tension during the foaming process. By controlling the nucleation and growth of bubbles, the pore size can be adjusted and made uniform. The specific steps include demolding pretreatment, melting, thickening, foaming and cooling solidification.

Benefits of technology

The pore size adjustment and distribution uniformity of aluminum foam were improved, enhancing the mechanical strength and thermophysical properties of the material. The porosity reached 88.4%, and the pore size variation coefficient was 0.49, significantly improving structural stability and energy absorption efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120818715B_ABST
    Figure CN120818715B_ABST
Patent Text Reader

Abstract

A preparation method of a specific pore size aluminum foam, comprising foaming, the foaming is adding a composite foaming agent and stearic acid in the tackified molten aluminum, and carrying out heat preservation foaming after stirring and dispersing, the composite foaming agent is titanium hydride as the main body, zirconium hydride and calcite as the adjuvant, and the mass ratio of titanium hydride, zirconium hydride and calcite is 5:1~2:0.5~0.8.In the application, TiH2, ZrH2 and calcite are used as the foaming agent, and the calcite is used in combination with stearic acid, so that the pore size structure and the uniformity of the pore distribution in the aluminum foam are controlled, the pore size is mainly distributed between 1~2mm, the pore size variation coefficient is 0.49, the porosity of the aluminum foam reaches 88.4%, the density retention rate of the material is between 108.2~120.4%, the structural stability is excellent, and the aluminum foam has obvious advantages as a heat and sound insulation material.The preparation process can be popularized to the preparation of aluminum-scandium alloy foam, so that the Sc distribution is promoted to be uniform, and the yield platform stress and the energy absorption efficiency are significantly higher than those of the pure aluminum foam.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of preparation of foamed aluminum and aluminum-scandium alloy foamed materials, and particularly relates to a preparation process of foamed aluminum with specific pore diameter. BACKGROUND

[0002] Foamed aluminum is a new type of material with both structural and functional characteristics, and has the properties of light weight, sound absorption, heat insulation, flame retardation, shock absorption, damping, energy absorption, electromagnetic shielding, etc., and is widely used in the fields of automobiles, rail transit, military equipment, aerospace, etc. Foamed aluminum is divided into closed-cell foamed aluminum and open-cell foamed aluminum according to the pore structure characteristics, and the pore size of closed-cell foamed aluminum is closely related to its performance, and the performance directly determines its application scenario. Research shows that the thermal conductivity of closed-cell foamed aluminum with a pore diameter of about 1 mm is 30% lower than that of traditional thermal insulation materials (such as rock wool), and the fireproof performance is better (the metal matrix is non-combustible), so it is often used for external wall thermal insulation of passive buildings. Therefore, closed-cell foamed aluminum with a pore diameter range of 1-2 mm has good heat and sound insulation performance, and is often used in building partition walls, pipeline insulation materials, sound barriers, etc.

[0003] The preparation of closed-cell foamed aluminum by the melt foaming method has the advantages of low cost, easy operation, and easy control of pore structure, and is suitable for industrial production. Foamed aluminum prepared by this method is often mainly prepared by using TiH2, ZrH2, etc. as thermal decomposition type foaming agent, and the quality of the foamed aluminum is closely related to the dispersion degree of the foaming agent. However, the wettability of aluminum melt and foaming agent is poor, and the foaming agent often aggregates, which affects the uniformity of the pore structure of the foamed aluminum, resulting in problems such as local large pores, relatively thick non-bubble layers, and gas escape, etc., thereby causing the mechanical strength of the foamed aluminum to decay, the thermophysical properties to deteriorate, and the functional characteristics to fail, etc. The existing technology often alleviates such defects by increasing the stirring rate or modification. For example, CN107254597A delays the decomposition temperature of TiH2 by coating it with phenolic resin to improve the dispersion and pore uniformity, but the decomposition of phenolic resin at high temperature will release toxic substances such as phenol and formaldehyde, which poses a health and environmental risk. For example, CN112746192A proposes to use magnesium carbonate and metal powder ball milling to prepare foaming agent to enhance the wettability of the melt and improve the uniformity of the pores, but magnesium carbonate has the characteristics of high decomposition temperature and low foaming efficiency, which is easy to cause insufficient porosity.

[0004] In general, the above methods have the problems of increasing the process cost and increasing the process complexity by modifying the foaming agent or the aluminum melt, and they have adverse effects on the performance or environment of the final product. Therefore, the selection of the foaming agent and the dispersion and foaming process of the foaming agent are helpful to prepare high-quality foamed aluminum and to control the pore diameter structure, pore diameter distribution and pore diameter size uniformity of the foamed aluminum. SUMMARY

[0005] In order to solve the problem that the foaming performance of the foaming agent is not controlled in the foaming process, the foaming performance is reduced, the pore size is difficult to adjust, and the pore size distribution and the pore size uniformity are poor in the process of preparing closed-cell aluminum foam by using the melt foaming method in the prior art, the present application aims to provide a preparation process of specific pore size aluminum foam, which improves the foaming performance of the foaming agent, improves the pore size adjustment and the pore size distribution uniformity of the aluminum foam, and improves the mechanical strength, the thermal physical properties and the functional characteristics of the material.

[0006] The object of the present application is achieved by the following technical solutions:

[0007] A preparation method of specific pore size aluminum foam, comprising demolding pretreatment, melting, viscosity increasing, foaming and cooling and solidification, characterized in that: the foaming is that the composite foaming agent and stearic acid are added into the molten aluminum after viscosity increasing, and the stirring and dispersion are carried out, and then the heat preservation foaming is carried out, the composite foaming agent is that titanium hydride is used as the main body, zirconium hydride and calcite are used as the auxiliary agent, and the mass ratio of the titanium hydride, the zirconium hydride and the calcite is 5:1~2:0.5~0.8.

[0008] Further, the mass ratio of the stearic acid and the calcite is 0.2~0.5:2.

[0009] Further, the composite foaming agent is divided into 5~15 equal parts, and then is wrapped into a ball shape by using aluminum foil, and the mass of each part of the foaming agent is 0.2wt.% of the aluminum liquid, and is added into the molten aluminum.

[0010] Further, the heat preservation foaming is that the heat preservation is first carried out at 500~600℃ for 3~5min, then the temperature is increased to 700~720℃ at a rate of 20~25℃ / min, and the heat preservation is carried out for 5~8min.

[0011] Further, the stirring and dispersion are carried out under the condition that the stirring is carried out at 1400~2200r / min for 15~35s.

[0012] Further, the molten aluminum is prepared by weighing the industrial pure aluminum, and heating at 680~750℃ for 1.5~2h.

[0013] Further, the viscosity increasing is that the granular Ca with a diameter of about 1.5mm is taken, the granular Ca is wrapped by using aluminum foil and is put into the molten aluminum, the stirring is carried out at a rotating speed of 1500~1600r / min for 1~3min, the heat preservation is carried out for 10~30min after the stirring is completed to obtain the mixed melt, and the mass of the granular Ca is 1~3% of the mass of the pure aluminum.

[0014] Most specifically, a preparation method of specific pore size aluminum foam, characterized in that, comprising the following steps:

[0015] (1) Demolding pretreatment: the demolding agent ZnO is emulsified by adding water, is applied on the inner wall of the stainless steel crucible, and is placed in a drying oven for drying at 100℃ for 2h;

[0016] (2) Melting: industrial pure aluminum is weighed and placed in a crucible, the crucible is placed in a pit furnace and heated at 680-750°C for 1.5-2h to ensure complete melting of the aluminum ingot;

[0017] (3) Tackifying: Ca particles with a diameter of about 1.5mm are weighed and wrapped with aluminum foil and then put into the molten aluminum, an elliptical three-blade stirring paddle (blade depression angle 45°, blade diameter 6mm) is pressed into the molten aluminum and stirred at a speed of 1500-1600r / min for 1-3min, and then the mixed melt is obtained after 10-30min of insulation, the mass of the Ca particles is 1-3% of the mass of the pure aluminum;

[0018] (4) Foaming: a composite foaming agent with a mass of 1-3% of the aluminum liquid is weighed, the foaming agent is equally divided into 5-15 parts, each part of the foaming agent is wrapped into a ball with aluminum foil, the mass of each part of the foaming agent is 0.2wt.% of the aluminum liquid, the size of the aluminum foil is 50mm×50mm, the temperature of the mixed melt is reduced to 500-600°C, the wrapped composite foaming agent is put into the mixed melt, stearic acid is added, the stirring paddle is quickly pressed and stirred at a speed of 1400-2200r / min for 15-35s, the stirring paddle is quickly removed after stirring, the furnace cover is covered and the foaming body is formed by segmental insulation, the composite foaming agent is composed of titanium hydride, zirconium hydride and calcite in a mass ratio of 5:1-2:0.5-0.8, the mass ratio of stearic acid and calcite is 0.2-0.5:2, and the segmental insulation is first insulated at 500-600°C for 3-5min, and then heated to 700-720°C at a rate of 20-25°C / min and insulated for 5-8min;

[0019] (5) Cooling and solidification: the crucible is taken out after the insulation is completed, the obtained foaming body is placed in a cooling barrel containing water to cool and solidify, and closed-cell aluminum foam with a pore size distribution of 1-2mm is obtained, and the liquid level of the cooling water is 5-8cm.

[0020] In the entire foaming process, at a temperature of 500-600°C, TiH2dominates the gas production and releases H2to form bubble nuclei, when the temperature is increased to 700-720°C, ZrH2dominates the gas production, and in this process, calcite continuously decomposes to produce gas and cooperates with stearic acid to adjust the strength of the bubble wall at each stage, thereby inhibiting bubble rupture and collapse or merging, thereby improving the uniformity of the pore size and the structural stability.

[0021] Compared with pure CaCO3, calcite has impurities such as MgCO3, so that the decomposition starting temperature is lower, the decomposition temperature range is wider, and the gas can be released at a lower temperature to foam, thereby reducing energy consumption, and the gas is generated and foamed during the whole insulation foaming process, which forms a favorable regulation for the foaming process. By utilizing the decomposition temperature difference between different components in calcite, a slow nucleation and rapid expansion foaming process is realized, and the uniformity of pore nucleation and growth is optimized. Secondly, MgO generated by the decomposition of calcite and stearic acid form a composite surface activity, stearic acid reduces the surface tension to promote bubble nucleation, MgO particles increase the strength of the bubble film and improve the interface stability, inhibit bubble merging or collapse, and realize the dual effect of rapid nucleation and long-term stability. Especially in high-porosity foamed aluminum, the structural stability can be improved.

[0022] The present application has the following technical effects:

[0023] In the present application, TiH2, ZrH2 and calcite are used as foaming agents, and calcite and stearic acid are combined to reduce the surface tension and promote bubble nucleation during the foaming process. The pore size structure and pore distribution uniformity in the foamed aluminum are regulated, the pore size is mainly distributed between 1-2mm, the pore size coefficient of variation is 0.49, and the porosity of the foamed aluminum is also improved, reaching 88.4%. The density retention rate of the material increases with the increase of strain, and is between 108.2-120.4%. The structural stability is excellent, and has obvious advantages as a heat and sound insulation material.

[0024] The closed-cell foamed aluminum prepared by the present application has a large specific surface area and through pores, and can provide a rapid mass transfer channel for subsequent vacuum Sc or Al-Sc melt infiltration-diffusion. The foamed aluminum preparation process can be applied to the preparation of aluminum-scandium alloy foam, which can promote the uniform distribution of Sc and the uniform precipitation of nanoscale Al3Sc strengthening phase, so that the yield platform stress and energy absorption efficiency are significantly higher than those of pure aluminum foamed aluminum. BRIEF DESCRIPTION OF DRAWINGS

[0025] Figure 1 The micro-morphology diagram of the foamed aluminum prepared in Example 1 of the present application.

[0026] Figure 2 The micro-morphology diagram of the foamed aluminum prepared in each comparative example.

[0027] Figure 3 The stress-strain curve of the static compression test of the foamed aluminum prepared in the examples and each comparative example. DETAILED DESCRIPTION

[0028] The application will be described in detail below by examples. It is necessary to point out here that the following examples are only used to further illustrate the application and cannot be understood as limiting the protection scope of the application. Those skilled in the art can make some non-essential improvements and adjustments to the application according to the above content of the application.

[0029] The calcite used in the application is common calcite with a purity of about 90%.

[0030] Example 1

[0031] A preparation method of mesoporous level foamed aluminum, comprising the following steps:

[0032] (1) demolding pretreatment: the demolding agent ZnO is emulsified with water, applied on the inner wall of the stainless steel crucible, and placed in a drying oven at 100℃ for 2h;

[0033] (2) melting: the industrial pure aluminum is weighed and placed in the crucible, and the crucible is placed in an 700℃ heating furnace for 1.5~2h to ensure that the aluminum ingot is completely melted;

[0034] (3) viscosity increase: the particles Ca with a diameter of about 1.5mm are weighed, wrapped with aluminum foil and put into the molten aluminum, and an elliptical three-blade stirring paddle (blade depression angle 45°, blade diameter 6mm) is used for pressing and stirring at a speed of 1550r / min for 2min, and after stirring, the mixed melt is obtained after 20min of heat preservation, and the mass of the particles Ca is 2% of the mass of the pure aluminum;

[0035] (4) foaming: the composite foaming agent with an aluminum liquid mass of 2% is weighed, and the foaming agent is equally divided into 10 parts, and then wrapped into a ball with aluminum foil, and the mass of each part of the foaming agent is 0.2wt.% of the aluminum liquid, and the size of the aluminum foil is 50mm×50mm, and after the temperature of the mixed melt is reduced to 550℃, the wrapped composite foaming agent is put into the mixed melt, and stearic acid is added, and the stirring paddle is quickly pressed and stirred at a speed of 2000r / min for 25s, and after stirring, the stirring paddle is quickly taken out, and the heating furnace cover is covered, and then the temperature is increased to 710℃ at a rate of 25℃ / min for 6min of heat preservation, and the foaming body is fully foamed to form a foamed body, and the composite foaming agent is composed of titanium hydride, zirconium hydride and calcite with a mass ratio of 5:1.5:0.6, and the mass ratio of stearic acid and calcite is 0.4:2;

[0036] (5) cooling and solidification: after the heat preservation is completed, the crucible is taken out, and the obtained foaming body is placed in a cooling barrel containing water for cooling and solidification, and a closed-cell foamed aluminum with a pore size distribution of 1~2mm is obtained, and the liquid level height of the cooling water is 8cm.

[0037] Comparative Example 1

[0038] Compared with Example 1, pure CaCO3 was used in the composite foaming agent to replace calcite with the same content of CaCO3 in calcite, and the remaining steps were the same as Example 1.

[0039] Comparative Example 2

[0040] Compared with Example 1, SDBS (sodium dodecyl benzene sulfonate) was used to replace stearic acid after adding the composite foaming agent in molten aluminum, and the remaining steps were the same as Example 1.

[0041] Comparative Example 3

[0042] Compared with Example 1, after adding the composite foaming agent and stearic acid in step (4), the temperature was increased to 710℃ at 10℃ / min and kept for 10 min after the holding at 550℃ was completed. The remaining steps were the same as Example 1.

[0043] The porosity, pore size, pore size uniformity and pore distribution uniformity of the foamed aluminum are key structural parameters affecting the energy absorption performance of the closed-cell foamed aluminum, and the mechanism involves stress distribution, energy dissipation path and failure mode of material deformation. The higher the uniformity of the pore size, the higher the uniformity of the pore wall deformation, and the energy absorption is concentrated in the platform area, while the poor uniformity of the pore size will lead to local densification in advance, and the platform area energy absorption will decrease. And uniform pore size and pore distribution make the buckling critical stress of the pore wall consistent, avoiding the problem of uneven energy dissipation caused by "weak hole collapse first, strong hole collapse later" due to poor pore size and distribution uniformity. In addition, the improvement of the uniformity of the pore distribution in the foamed aluminum can uniformly transmit the load to the entire material, improving the stability of the overall compressive and tensile strength. The pore structure of the foamed aluminum prepared in Example 1 is shown in Figure 1 As can be seen, the prepared foamed aluminum has uniform voids and excellent pore size distribution uniformity, mainly distributed in the range of 1-2mm. The pore structure of the foamed aluminum prepared in Comparative Examples 1-3 is shown in Figure 2 As can be seen, the pore size uniformity of the prepared foamed aluminum is poor, and the pore size distribution uniformity is also not ideal.

[0044] In addition to being observed by scanning electron microscopy, pore size distribution can also be calculated. Pore size uniformity is represented by data: the internal pore structure image of the foamed aluminum is obtained by CT scanning, and the image is processed by image j image processing software to calculate the pore size in the image. After obtaining the pore size, the coefficient of variation of the pore size is calculated to represent the pore size uniformity, and the calculation formula is:

[0045]

[0046] In the formula, The smaller the coefficient of variation of the pore size, the more similar the pore size is, and the more uniform the pore size distribution is;

[0047] The standard deviation;

[0048] The average value of the pore size.

[0049] The higher the porosity of the aluminum foam is, the wider the energy absorption platform area is, and the porosity is measured by the drainage method, and the calculation formula is as follows:

[0050]

[0051] In the formula, Ø is the porosity;

[0052] m is the sample mass, g;

[0053] ρAl is the density of the aluminum matrix (pure aluminum), g / cm 3 ;

[0054] V is the sample drainage volume, cm 3 .

[0055] The test results are shown in Table 1.

[0056] Table 1:

[0057]

[0058] It can be known by calculation that the pore size coefficient of variation of the aluminum foam prepared in Example 1 is 0.49, and the pore size coefficients of variation of the other comparative examples are significantly increased. It is shown that the uniformity of the pore size of the aluminum foam in Example 1 is excellent. It can be seen from the above table that the porosity of the closed-cell aluminum foam prepared in Example 1 reaches 88.4%, and the porosities of the aluminum foams prepared in Comparative Example 1, Comparative Example 2 and Comparative Example 3 are 76.7%, 74.3% and 78.9% respectively, which obviously decreases compared with Example 1.

[0059] The energy absorption mechanism of the closed-cell aluminum foam mainly depends on the plastic deformation and elastic deformation of the porous structure. The energy absorption density and energy absorption performance efficiency of each group of aluminum foams are tested by a static compression test (static energy absorption detection), and the results are shown in Table 2.

[0060] Table 2:

[0061]

[0062] It can be seen that the static energy absorption density of the aluminum foam prepared in Example 1 reaches 10.46 MJ / m 3, the maximum energy absorption efficiency reaches 0.74, and the energy absorption density and the maximum energy absorption efficiency of the other comparative examples are obviously decreased. The stress-strain curves of the static compression test of the foamed aluminum prepared in Example 1 and each comparative example are shown in FIG. 2. Figure 3

[0063] In addition, the density retention rate is a "visual index" of the mechanical properties and structural stability of foamed aluminum. The density retention rate is the ratio of the remaining density to the original density after foamed aluminum is subjected to force (such as compression, impact) or environmental action (such as high temperature, aging), and is usually expressed as a percentage:

[0064] Density retention rate = (Density after loading / Density before loading) x 100%

[0065] Thermal and sound insulation materials rely on air layers in the porous structure to block the transmission of heat or sound. If the density retention rate is low (i.e., the porosity retention after loading is high), the air layer is more complete, and the thermal / sound insulation performance is better; if the density retention rate is too high (i.e., the pore collapse is serious), the air layer is reduced, and the performance is decreased. The uniformity of pore size and the uniformity of pore distribution in foamed aluminum will significantly affect the degree of pore collapse during stress and strain, thereby affecting the change of density retention rate. In the above stress and strain test process, the porosity retention effect of the foamed aluminum in Example 1 is excellent, and in the process of static energy absorption detection, the density retention rate fluctuates between 108.2~120.4% with the increase of strain, while the density retention rate of Comparative Example 1, Comparative Example 2 and Comparative Example 3 changes between 167.8~356.7%, 151.6~327.5% and 159.5~342.9% respectively with the increase of strain in the process of static energy absorption detection and dynamic energy absorption detection. The change of density retention rate can evaluate the anti-compaction ability of foamed aluminum.

[0066] Example 2

[0067] A method for preparing a mesoporous foamed aluminum, comprising the following steps:

[0068] (1) Demolding pretreatment: add demolding agent ZnO to water, emulsify, and apply on the inner wall of a stainless steel crucible, and then place in a drying oven at 100°C for 2h;

[0069] (2) Melting: weigh industrial pure aluminum and place in the crucible, and then place the crucible in an 680°C heating furnace for 2h to ensure complete melting of the aluminum ingot;

[0070] (3) Tackifying: weigh granular Ca with a diameter of about 1.5mm, wrap with aluminum foil, and then drop into the molten aluminum, press with an elliptical three-blade stirring paddle (blade depression angle 45°, blade diameter 6mm), and then stir at a speed of 1500r / min for 3min, and then keep warm for 10min to obtain a mixed melt, and the mass of the granular Ca is 1% of the mass of the pure aluminum; ​​

[0071] (4) Foaming: 3% of the aluminum liquid mass of the composite foaming agent is weighed, the foaming agent is equally divided into 15 parts, and is wrapped into a ball shape using aluminum foil. The mass of each foaming agent is 0.2wt.% of the aluminum liquid, and the size of the aluminum foil is 50mmx50mm. After the temperature of the mixed melt is reduced to 500℃, the wrapped composite foaming agent is put into the mixed melt, and stearic acid is added. The stirring paddle is quickly pressed and stirred at 1400r / min for 35s. After stirring, the stirring paddle is quickly removed, the heating furnace cover is covered, and the temperature is first maintained at 500℃ for 5min, and then increased to 700℃ at a rate of 20℃ / min, and maintained for 8min to form a foam body. The composite foaming agent is composed of titanium hydride, zirconium hydride, and calcite in a mass ratio of 5:1:0.8, and the mass ratio of stearic acid and calcite is 0.2:2.

[0072] (5) Cooling and solidification: after the heat preservation is completed, the crucible is taken out, and the obtained foaming body is placed in a cooling barrel containing water to cool and solidify, so as to obtain closed-cell aluminum foam with a pore size distribution of 1-2mm. The liquid level of the cooling water is 6cm.

[0073] Example 3

[0074] A method for preparing mesoporous aluminum foam, comprising the following steps:

[0075] (1) Demolding pretreatment: the demolding agent ZnO is emulsified with water, and is applied to the inner wall of the stainless steel crucible, and is placed in a drying oven at 100℃ for 2h;

[0076] (2) Melting: industrial pure aluminum is weighed and placed in the crucible, and the crucible is placed in an 750℃ heating furnace for 1.5h to ensure that the aluminum ingot is completely melted;

[0077] (3) Tackifying: particles of Ca with a diameter of about 1.5mm are weighed, wrapped with aluminum foil, and put into the molten aluminum. An elliptical three-blade stirring paddle (blade depression angle 45°, blade diameter 6mm) is used to press and stir at a speed of 1600r / min for 1min. After stirring, the mixed melt is obtained by heat preservation for 30min. The mass of the particles of Ca is 3% of the mass of the pure aluminum;

[0078] (4) Foaming: 1% of the composite foaming agent of the aluminum liquid is weighed, the foaming agent is equally divided into 5 parts, and is wrapped into a ball with aluminum foil, the mass of each part of the foaming agent is 0.2wt.% of the aluminum liquid, the size of the aluminum foil is 50mm*50mm, the temperature of the mixed melt is reduced to 600℃, then the wrapped composite foaming agent is put into the mixed melt, stearic acid is added, the stirring paddle is quickly pressed and stirred, the stirring is carried out at 2200r / min for 15s, the stirring paddle is quickly taken out after the stirring is completed, the heating furnace cover is covered, the temperature is first kept at 600℃ for 3min, then the temperature is increased to 720℃ at a rate of 20℃ / min, and is kept for 5min, the composite foaming agent is fully foamed to form a foam body, the composite foaming agent is composed of titanium hydride, zirconium hydride and calcite according to a mass ratio of 5:1:0.5, the mass ratio of stearic acid and calcite is 0.2:2;

[0079] (5) Cooling and solidification: after the heat preservation is completed, the crucible is taken out, the obtained foaming body is placed in a cooling barrel containing water to cool and solidify, closed-cell aluminum foam with a pore size distribution of 1-2mm is obtained, and the liquid level of the cooling water is 5cm.

Claims

1. A method for preparing aluminum foam with a specific pore size, comprising demolding pretreatment, melting, thickening, foaming, and cooling solidification, characterized in that: The foaming process involves adding a composite foaming agent and stearic acid to molten aluminum after thickening. The composite foaming agent is divided into 5-15 equal parts by mass, which are then wrapped in aluminum foil to form spherical shapes. Each part of the foaming agent has a mass of 0.2 wt.% of the molten aluminum and is dispersed into the molten aluminum. After stirring and dispersing, the mixture is subjected to heat preservation foaming. The heat preservation foaming process involves first holding the temperature at 500-600℃ for 3-5 minutes, and then raising the temperature to 700-720℃ at a rate of 20-25℃ / min and holding it for 5-8 minutes. The composite foaming agent is mainly composed of titanium hydride, with zirconium hydride and calcite as additives. The mass ratio of titanium hydride, zirconium hydride and calcite is 5:1-2:0.5-0.8, and the mass ratio of stearic acid and calcite is 0.2-0.5:

2. This method prepares closed-cell aluminum foam with a pore size distribution of 1-2 mm.

2. The method for preparing aluminum foam with a specific pore size as described in claim 1, characterized in that: The stirring and dispersion is carried out at 1400~2200 r / min for 15~35 s.

3. The method for preparing aluminum foam with a specific pore size as described in claim 2, characterized in that: The molten aluminum is obtained by weighing industrial pure aluminum and heating it at 680~750℃ for 1.5~2 hours.

4. The method for preparing aluminum foam with a specific pore size as described in claim 3, characterized in that: The thickening process involves taking Ca particles with a diameter of approximately 1.5 mm, wrapping them in aluminum foil, and adding them to molten aluminum. The mixture is stirred at a speed of 1500-1600 r / min for 1-3 min, and then kept at a temperature of 10-30 min to obtain a mixed melt. The mass of the Ca particles is 1-3% of the mass of pure aluminum.

5. A method for preparing aluminum foam with a specific pore size, characterized in that, Includes the following steps: (1) Demolding pretreatment: emulsify the release agent ZnO with water, apply it to the inner wall of the stainless steel crucible, and dry it in a drying oven at 100°C for 2 hours; (2) Melting: Weigh out industrial pure aluminum and place it in a crucible. Put the crucible into a pit-type heating furnace and heat it at 680~750℃ for 1.5~2 hours to ensure that the aluminum ingot is completely melted; (3) Thickening: Weigh Ca particles with a diameter of about 1.5 mm, wrap them in aluminum foil and put them into molten aluminum. Use an elliptical three-bladed stirring paddle with a blade downward angle of 45° and a blade diameter of 6 mm to press and stir. Stir at a speed of 1500~1600 r / min for 1~3 min. After stirring, keep warm for 10~30 min to obtain a mixed melt. The mass of the Ca particles is 1~3% of the mass of pure aluminum. (4) Foaming: Weigh 1-3% of the composite foaming agent by weight of the molten aluminum, divide the foaming agent into 5-15 equal portions, and then wrap each portion in aluminum foil to form a ball. Each portion of foaming agent has a mass of 0.2 wt.% of the molten aluminum, and the aluminum foil size is 50 mm × 50 mm. After the temperature of the mixed melt is reduced to 500-600℃, add the wrapped composite foaming agent into the mixed melt, add stearic acid, and quickly press down the stirring paddle to stir. Stir for 15-30 minutes at 1400-2200 r / min. After stirring for 5 seconds, quickly remove the stirring paddle, cover the heating furnace with the lid and keep it warm in sections to fully foam and form a foam body. The composite foaming agent is composed of titanium hydride, zirconium hydride and calcite in a mass ratio of 5:1~2:0.5~0.8, and the mass ratio of stearic acid and calcite is 0.2~0.5:

2. The section heat preservation is to first keep it at 500~600℃ for 3~5 minutes, and then raise the temperature to 700~720℃ at a rate of 20~25℃ / min and keep it warm for 5~8 minutes. (5) Cooling and solidification: After the heat preservation is completed, the crucible is removed and the obtained foam is placed in a water-filled cooling tank for cooling and solidification to obtain closed-cell aluminum foam with a pore size distribution of 1~2mm and a cooling water level of 5-8cm.

Citation Information

Patent Citations

  • Boron phenolic resin modified foam aluminum foaming agent and preparation method thereof

    CN107254597A

  • Foaming agent, preparation method, and method for preparing foamed aluminum or foamed aluminum alloy

    CN112746192A

  • Preparation method of small pore diameter foamed aluminium

    CN101182608A

  • Nano-ceramic particle reinforced aluminum foam matrix composite material and preparation method thereof

    CN101876017A